The ethnocultural meaning of the artifacts of the Karachay-Balkarian wedding: the processes of desemantization and increment - Bakhtikireeva, Uldanai M.; Bashieva, Svetlana K. (The New Research of Tuva, 2025)
The article examines an aspect of the study of Karachay-Balkar wedding rituals — namely, the desemantization and the accretion of ethnocultural meanings in artifacts directly or indirectly related to wedding ceremonies. The empirical material was collected through a sampling method of object and phenomenon names drawn from documentary, lexicographic, ethnographic, and folkloric sources. It includes nominations of two types of artifacts: “pre-wedding” and wedding related. The embedded ethnocultural meanings of “pre-wedding” artifacts serve to realize various functions, including value-orientational, regulatory, and axiological, as well as intergenerational transmission. These artifacts can be classified into those that remain relevant and function within the contemporary life of the ethnic group, and those that are no longer relevant preserved within the linguistic system as historicisms and archaisms that have since been replaced. In the past, various items were considered essential to matchmaking rituals. While not directly related to the wedding ceremony itself, their accompanying function was rooted in the non-verbal information they conveyed — information that had to be “read” and interpreted appropriately by the matchmakers. A number of these artifacts vividly illustrate the process of desemantization of ethnocultural meaning, as they are no longer decoded in the same way as before.